OMNIBUS LAW COPYRIGHT WORK REVIEWED FROM THE PHILOSOPHY OF LAW - Sofian; Rasji (Awang Long Law Review, 2021)
This research aims for omnibus law copyright work reviewed from the philosophy of law. The research method used is normative legal research. Research is descriptively analytical. Data collection techniques are carried out by way of literature studies. The results of the study showed the Omnibus Law Copyright Work Reviewed From the Philosophy of Law, it is seen that the Law to be created through the establishment of omnibus copyright law only pursues legal certainty in the field of the investment itself and forgets the principle of justice. Where the government's current goal continues to encourage the entry of foreign investors into the country, this can be seen from the onslaught of government actions, including omnibus law regulations and policies. Omnibus Law is known in Indonesia after the President of Indonesia delivered it in a state of the nation address at his inauguration as President before the MPR session on October 20, 2019. Omnibus law is the focus of the president to solve the problem of overlapping regulations and bureaucracy. The hope is that the omnibus law can provide good service for the community and attract foreign investors to invest in Indonesia.